Study of saline wastewater influence on activated sludge flocs through automated image analysis - Mesquita, D. P. (2009)
BACKGROUND: In activated sludge systems, sludge settling ability is considered a critical step in effluent quality and determinant of solid-liquid separation processes. However, few studies have reported the influence of saline wastewater on activated sludge. This work aims the evaluation of settling ability properties of microbial aggregates in a sequencing batch reactor treating saline wastewaters of up to 60 g L-1 NaCl, by image analysis procedures. RESULTS: It was found that the sludge volume index (SVI) decreased with salt content up to 20 g L-1, remaining somewhat stable above this value. Furthermore, it was found that between the first salt concentration (5 g L-1) and 20 g L-1 aggregates suffered a strong deflocculation phenomenon, leading to a heavy loss of aggregated biomass. Regarding SVI prediction ability, a good correlation coefficient of 0.991 between observed and predicted SVI values was attained. CONCLUSION: From this work the deflocculation of aggregated biomass with salt addition due to pinpoint floc formation, dispersed bacteria growth and protozoa absence could be established. With respect to SVI estimation, and despite the good correlation obtained, caution is advisable given the low number of SVI data points.